Inclusive Education in Indonesia from The Perspective of Widyaiswara in Center for Development and Empowerment of Teachers and Education Personnel of Kindergartens and Special Education - Ediyanto Ediyanto; Iva Nandya Atika; Norimune Kawai; Edy Prabowo (Indonesian Journal of Disability Studies, 2017)
Since 2009, Indonesia has an excellent commitment and effort in the field of inclusive education. The government provides equal opportunities in education. Through Centre for Development and Empowerment of Teachers and Education Personnel of Kindergartens and Special Education (PPPPTK TK & PLB), the government provides training and services to teachers in the field of inclusive education and special education. The teacher trainers in PPPPTK TK & PLB are called WidyaIswara. The purpose of this study is to know the implementation of inclusive education in Indonesia from the perspective of WidyaIswara of PPPPTK TK & PLB. The research used qualitative method. This research was conducted on March 2nd, 2017 in PPPPTK TK & PLB located in Bandung, Indonesia. Data were collected using a questionnaire in the interview related to perceptions about special and inclusive education. The interview process used the instrument in interview form to experts that called WidyaIswara with closed-ended questions. A total of 3 Expert in Inclusive Education in PPPPTK participated in this activity. From the findings and discussion of the research, explained about WidyaIswara's perception about: 1) Awareness of students to go to school, 2) Grouping of students with special needs in special and general schools, 3) Distribution of Special Schools in Indonesia, 4) Supporting educational facilities and infrastructure in special and inclusive schools, 5) Teacher in special and inclusive Schools, 6) Learning Activities, 7) Children with special needs after graduation at a level of education, and 8) Government efforts.